THE INFLUENCE OF THE TALKING STICK METHOD ASSISTED BY MISTERY BOX MEDIA IN IMPROVING INDONESIAN SPEAKING SKILLS IN CLASS V AT MIS MUSLIMAT NU PALANGKA RAYA - Khofifah Farawansa; Mila; Muhammad Syabrina (SOSIOEDUKASI, 2026)
The purpose of this study is to describe the implementation of the Talking Stick method in class V of Indonesian subjects at MIS Muslimat NU using Mystery Box media, ensuring student learning outcomes after the implementation of the method. The quasi-experimental design more specifically, the Design of Non-Equivalent Control Groups became the basis of the quantitative methodology of this study. Meanwhile, the findings of this study show that the Talking Stick method has been used to improve speaking skills and learning outcomes in experimental classrooms through independent learning based on conventional methods and strengthening face-to-face materials with the help of Mystery Box media which has increased (significantly). There was a marked difference between the learning capacity of the two groups, according to the significance criteria Based on the results of the Shapiro-Wilk normality test, the scores of students in class VA and class VB had significance values of 0.800 and 0.238, respectively. It can be concluded that the students' scores in the VA and VB classes are normally distributed because both significance values > 0.05. With the right infrastructure and student readiness levels, the Talking Stick method can be an effective alternative learning paradigm as well as increase student engagement in classroom learning.